CHARACTERIZATION OF FLUORESCENT PSEUDOMONAS STRAINS FOR THEIR ACC DEAMINASE AND KMBA PATHWAYS - CHAUBEY S.,; G.ARCHANA, (International Journal of Pharma and Bio Sciences, 2015)
Present work deals with the characterization of isolated fluorescent pseudomonads based on their ability to utilize an unusual nitrogen source (e.g. 1-aminocyclopropane-1-carboxylate (ACC), L- methionine, α-keto γ-methylthiobutyric acid, KMBA) or other xenobiotic compound which provide a competitive advantage over other microorganisms in the rhizosphere. Most of isolated fluorescent pseudomonad showed the utilization of L- methionine as nitrogen source, while some rhizobacterial strain have utilized ACC as nitrogen source and only few strains e.g. G13, G29, G35, H4 and H9 showed the ability to utilize both ACC and L-MET as a nitrogen source and proved that both pathway is functional in these organisms. Most of isolated fluorescent pseudomonad showed the ability of ethylene production from deamination of L- methionine to produce α-keto γ-methylthiobutyric acid (KMBA). ACC deaminase activity was quantified in the strains and showed ACC deaminase activity at the range of 1-21 ug of α-ketobutyrate/mg of protein. Isolated fluorescent pseudomonad has shown high indole acetic acid (IAA) production at the range of 33-43µg/ml. Strain G29 has shown good ACC deaminase production as well as possess both L-methionine and ACC utilization pathway and thus it enhance the survival ability of these strains in the rhizosphere. So these strains could be considered as good PGPR strains for the application.